The 4Rs Framework: Creating A Synergy to Support the Implementation of English Education for Sustainable Development in Rwanda - Chidakwa, Nowell (Research in Social Sciences and Technology, 2024)
Rwanda started teaching English to support sustainable development and deliver the five key pillars that will help Rwandans transition from their existing way of life to the society they all desire and are happy to be a part of. As a follow-up to the Sustainable Development Goals and the Berlin Declaration on Education for Sustainable Development, the government ensured the standardisation and teaching of English. In order to assist the implementation of English teaching nationally, the theoretical paper explains how the 4Rs Framework—relationship-building, recognition, responsibilities, and reciprocity—combine to generate synergy among many stakeholders and cross-sectoral collaboration. The study presents literature on Rwanda's Vision 2050, education for sustainable development, and teaching using English as a medium of communication. It is founded on a critical literature review. The article discusses options for national transformation while emphasising the importance of locally rooted collaboration. The 4Rs technique is intended to foster discussion among important players about the issues and problems facing the area of education in emergencies rather than serving as a rigid theoretical framework. The study shows the connections between and tensions among the various "Rs," as well as the efficiency of the 4R dimensions in encouraging the teaching of English. The study considered ways to get beyond the approach's drawbacks and difficulties to support sustainable schooling in Rwanda. This framework encourages the creation of a synergistic educational ecosystem that equips students with the information, skills, and attitudes required to actively participate in Rwanda's path to sustainable development.